The meta-gut: community coalescence of animal gut and environmental microbiomes - Dutton, Christopher L.; Subalusky, Amanda L.; Sanchez, Alvaro; Estrela, Sylvie; Lu, Nanxi; Hamilton, Stephen K.; Njoroge, Laban; Rosi, Emma J.; Post, David M. (Scientific reports, 2021)
All animals carry specialized microbiomes, and their gut microbiota are continuously released into the environment through excretion of waste. Here we propose the meta-gut as a novel conceptual framework that addresses the ability of the gut microbiome released from an animal to function outside the host and alter biogeochemical processes mediated by microbes. We demonstrate this dynamic in the hippopotamus (hippo) and the pools they inhabit. We used natural field gradients and experimental approaches to examine fecal and pool water microbial communities and aquatic biogeochemistry across a range of hippo inputs. Sequencing using 16S RNA methods revealed community coalescence between hippo gut microbiomes and the active microbial communities in hippo pools that received high inputs of hippo feces. The shared microbiome between the hippo gut and the waters into which they excrete constitutes a meta-gut system that could influence the biogeochemistry of recipient ecosystems and provide a reservoir of gut microbiomes that could influence other hosts. We propose that meta-gut dynamics may also occur where other animal species congregate in high densities, particularly in aquatic environments.